Analisis Faktor Project Based Learning Melalui Grand Teori S-O-R pada Manajemen Pemasaran - Suryadi; Joko Samboro; Dika Rizky Yunianto (Jurnal Akuntansi Bisnis Dan Humaniora, 2023)
Changes in the Independent Curriculum Free Learning in the Industrial Revolution Era 4.0 is a challenge for changing the learning paradigm, communicating the affective domain in the Gradation of Attitudes, Knowledge and skills that require the concept of Stimulus Organism Response. Implementation of this learning is a continuation of Blended in type discovery and problem base learning (Suryadi, et al 2020) which shows a very effective impact for project tasks according to industry needs. Project based learning is a scientific learning model that emphasizes students to learn to find and discover for themselves an incomplete concept or principle. The research objective is to analyze the dominant factors of the Marketing Management project base learning model. This research method is "Four-D", the sampling technique uses probability sampling techniques and data collection techniques using observation methods, learning (Project Based Learning), pretest & post test methods, and questionnaire methods. Factor analysis data analysis techniques. Findings of social attitudes, motivation and activity as determinants of achievement for which 75 statements in order of importance (1) Social attitudes of 25 questions with a factor loading value of 0.5 to 0.89 (2) Motivation a number of 12 questions with a loading factor value of between 0.60 to 0.80 (3) The activity of a number of 4 question items with a loading factor value between 0.56 to 0.63. Project Based Learning is suitable for vocational.